Impact of Ethrel, Crop Geometry and Fruit Load onSeed Yield and Quality in Bottle Gourd - ABHILASHA; RAJINDER SINGH2 (Seed Research, 2026)
The present investigation entitled “Influence of ethrel, crop geometry and fruit load on seed yield and quality in bottle gourd (Lagenaria siceraria (Mol.) Standle.)” was conducted at Experimental Research Farm and Seed Physiology Laboratory, Office of Director (Seeds), PAU, Ludhiana during February to July 2019 and 2020. The experiment was laid out in factorial randomized block design keeping three row spacings (250 x 50, 225 x 50 and 200 x 50 cm), three ethrel treatment at 2-4 leaf stage (50 ppm, 100 ppm and control) and number of fruits to be retained per plant (1, 2 and 3 fruits). The results revealed that at 250 x 50 cm spacing maximum vine length (cm), number of filled seeds,100 seed weight (g), number of seeds per fruit, seed yield per plant (g) and per hectare (q) and germination percentage was observed, but number of unfilled seeds were minimum and were comparable at 225 x 50 cm spacings. With ethrel application at 50 ppm concentration maximum number of filled seeds, hundred seed weight (g), seed number per fruit, seed yield per plant (g) and per hectare (q), germination percentage were observed but number of days and number of nodes for first male and female flower was decreased. Retaining one fruit per vine length improved hundred seed weight (g), number of seeds per fruit, number of filled seeds, germination percentage, but seed yield per plant, seed yield per hectare (q) were maximum with retention of two fruits per vine. It may be concluded that maximum seed yield and quality of bottle gourd seed was obtained when they were spaced at 225 x 50 cm and sprayed with ethrel @ 50 ppm at 2 and 4 leaf stage and two fruits per vine were retained.